Parallel hybrid static synchronous series compensator - SONG JIEYING; LU ZHENGANG; DAI ZHAOBEI; DENG ZHANFENG; YU ZHIYONG; ZHAO GUOLIANG; CAI LINHAI (2016)
The invention provides a parallel hybrid static synchronous series compensator, which comprises a converter, a fixed offset compensation device and a series transformer, wherein the converter is connected to a power transmission line in series; the fixed offset compensation device is connected with the converter in parallel; or the converter is connected with one side winding of the series transformer in parallel; the other side winding of the series transformer is connected to the power transmission line; two ends of the side winding are connected with a first bypass switch in parallel; and the fixed offset compensation device is connected with the converter in parallel or connected with the other side winding in parallel. Compared with the prior art, the parallel hybrid static synchronous series compensator provided by the invention has the advantages that the capacity required by the converter can be significantly reduced; the cost is reduced; and meanwhile, the parallel hybrid static synchronous series co